"Localization" in Fragile Spaces: A Comparative Networks Evaluation of Community-Based Programmes in Pakistan and Afghanistan. Issue 1 (2nd January 2022) - Khwaja, Elsa Talat
ABSTRACT: Conventional externally-driven development interventions have shifted towards 'localized, ' 'bottom-up, ' participatory approaches, such as Community-Driven Development (CDD). However, structural dynamics of conflict-prone spaces continue to challenge their sustainability. Integrating content analysis, social network analysis (SNA), and qualitative comparisons (archival research and over 100 field interviews), this article examines the efficacy of CDD in Pakistan and Afghanistan. SNA of two World Bank programmes illuminates network properties of power and centralization, corresponding with key insights from fieldwork, including comparisons with Pakistan's Rural Support Programmes. This mixed-method study reveals critical structural conditions that permit and/or constrain sustainable, locally-owned processes in fragile spaces.